Modern ICT for the Rural Growth and Development - Verma, Deepti; Ambhaikar, Asha (International Journal of Computer Sciences and Engineering, 2025)
Information and communications technology (ICT) mention to all the technology used to handle telecommunications, broadcast media, intelligent building management systems, audiovisual processing and transmission systems, network-based control and monitoring functions. Networks have combined the services of telephone, television and computer networks requiring different infrastructure and channels into a single communication network. Modern information and communication technologies created a "smart village," in which people can communicate with others across the world as if they were living next door. Objective of proposed paper is to focus on growth and development of rural area with ICT.